The disease-specific clinical trial network for primary ciliary dyskinesia: PCD-CTN. Issue 3 (15th August 2022) - Raidt, Johanna; Maitre, Bernard; Pennekamp, Petra; Altenburg, Josje; Anagnostopoulou, Pinelopi; Armengot, Miguel; Bloemsma, Lizan D.; Boon, Mieke; Borrelli, Melissa; Brinkmann, Folke; Carr, Siobhan B.; Carroll, Mary P.; et al.
Primary ciliary dyskinesia (PCD) is a rare genetic disorder characterised by impaired mucociliary clearance leading to irreversible lung damage. In contrast to other rare lung diseases like cystic fibrosis (CF), there are only few clinical trials and limited evidence-based treatments. Management is mainly based on expert opinions and treatment is challenging due to a wide range of clinical manifestations and disease severity. To improve clinical and translational research and facilitate development of new treatments, the clinical trial network for PCD (PCD-CTN) was founded in 2020 under the framework of the European Reference Network (ERN)-LUNG PCD Core. Applications from European PCD sites interested in participating in the PCD-CTN were requested. Inclusion criteria consisted of patient numbers, membership of ERN-LUNG PCD Core, use of associated standards of care, experience in PCD and/or CF clinical research, resources to run clinical trials, good clinical practice (GCP) certifications and institutional support. So far, applications from 22 trial sites in 18 European countries have been approved, including >1400 adult and >1600 paediatric individuals with PCD. The PCD-CTN is headed by a coordinating centre and consists of a steering and executive committee, a data safety monitoring board and committees for protocol review, training and standardisation. A strong association with patient organisations and industrial companies are further cornerstones. All participating trial sites agreed on a code of conduct. As CTNs from other diseases have demonstrated successfully, this newly formed PCD-CTN operates to establish evidence-based treatments for this orphan disease and to bring new personalised treatment approaches to patients. The disease-specific clinical trial network for primary ciliary dyskinesia (PCD-CTN) was built under the framework of the European Reference Network (ERN)-LUNG PCD Core, and operates to establish evidence-based and new personalised treatment for PCD https://bit.ly/3sLtC8o